Problematika Pembelajaran Tematik: Studi Kasus Di Sdn 1 Banu Banua Jaya - Ilham Muhammad; Raehang Raehang; Ilan Sari (Jurnal Sultra Elementary School, 2022)
This study aims to identify the problems encountered in implementing thematic learning at SDN 1 Banua Banua Jaya. The research employed a qualitative approach with six teachers as research informants. Data were collected through observations and interviews. The findings revealed that the implementation of thematic learning at SDN 1 Banua Banua Jaya has not been carried out optimally. In the planning stage, teachers had not prepared lesson plans properly. During the implementation stage, thematic learning was not conducted as intended — learning was teacher-centered and the material was presented separately rather than integrated. In the assessment stage, teachers only assessed knowledge and skills, while the assessment of attitudes had not been implemented. The main challenges faced by teachers included the lack of teacher and student textbooks, limited facilities and infrastructure, and low understanding of thematic learning. To address these issues, the school has taken several steps such as sending teachers to attend curriculum 2013 seminars and training, encouraging participation in teacher working groups (KKG), and holding collaborative discussions among teachers at school.